Pedagogical Technologies of Teaching Fifth and Sixth Grade Students Ecological Culture Through the Laboratory Work “Sociological Survey “Me and Nature” (Journal of Educational Sciences, 2025)
There are many experimental, laboratory, practical classes in natural science textbooks, which are taught to students of general education schools in the fifth and sixth grades. It is by teaching these lessons using effective pedagogical methods that it is possible to arouse students’ interest in this subject. The article examines the use of laboratory work and sociological questionnaires as pedagogical technologies for teaching sixth grade students to ecological culture. The study aims to develop students’ environmental awareness as well as their ability for sustainable behavior. The article presents the theoretical foundations of environmental culture, laboratory work and sociological surveys, as well as the practical implementation of the study. Students of the fifth and sixth grade of school-gymnasium No. 81 of Bostandyk District of Almaty took part in the research work. The study consisted of two parts. In the first part, students were divided into 3 groups, one took a questionnaire, the other answered, and the third processed and analyzed the answers. In the second part of the study, students took a survey of residents of the the Koktem microdistrict of Bostandyk District of Almaty. Students, with the help of subject teacher, processed the answers, analyzed and built models. At the end of the laboratory lesson, feedback was received from students. 100% of the students answered that the lesson was “very interesting”. The results show that the use of laboratory work and sociological questionnaires is an effective way for students to form an environmental culture, as it allows them to actively engage and apply theoretical concepts in practice. The study ends with recommendations for further research and pedagogical practice.Key words: survey, natural Science subject, ecological culture, man and nature, laboratory lesson, analyzes, model construction, pedagogical methods.